Administrative Law Implementation on Ethical Misconduct in Government Institutions: Implementasi Hukum Administrasi terhadap Pelanggaran Etika dalam Lembaga Pemerintahan - Allicya Dea Rachel; Feni Aura Fadillah; Yohana Posma L. Sihombing (Academia Open, 2025)
Background: Ethical violations by government personnel remain a persistent challenge that undermines legal integrity and public trust. Specific background: Cases involving corruption, abuse of authority, and narcotics misuse within military environments reveal the complexity of administrative and disciplinary mechanisms. Knowledge gap: Limited studies address how State Administrative Law functions when ethical violations occur within military institutions. Aims: This study analyzes the application of administrative legal instruments in responding to severe ethical violations committed by government personnel, including military officers. Results: The findings show that administrative law provides a structured framework for ensuring accountability through sanctions, supervision, and adherence to legality and professional standards, although its implementation is hindered by weak oversight, permissive bureaucratic culture, and political intervention. Novelty: This research integrates ethical perspectives with administrative legal mechanisms in cases involving military actors, offering an administrative viewpoint beyond conventional military criminal analysis. Implications: Strengthening technical guidelines, institutional coordination, and ethical culture is necessary for reinforcing administrative accountability and promoting principled governance within public institutions. Highlights: • Administrative law serves as a framework for addressing ethical misconduct in government institutions. • Ethical violations within military settings reveal gaps in administrative oversight and institutional coordination. • Strengthening guidelines and ethical culture enhances accountability in public administration. Keywords: State Administrative Law, Professional Ethics, Government Accountability, Administrative Sanctions, Public Governance